2023
DOI: 10.1097/jcma.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of liver transplantation for alcohol-related liver disease

Abstract: Background: Liver transplantation (LT) is being increasingly performed for alcohol-related liver disease (ALD). It is unclear whether the increasing frequency of LTs in ALD patients has a negative impact on deceased-donor (DDLT) allocation and whether the current policy of 6 months of abstinence before transplantation effectively prevents recidivism after transplantation or improves long-term outcomes. Methods: A total of 506 adult LT recipients, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…[3] In a 2023 study of 506 LT recipients (97 of whom had ALD), 1 year, 3 year, and 5 year survival rates posttransplant were also similar (87.7%/84.3%/79.5% for ALD group vs. 82.8%/76.6%/ 72.2% in the non-ALD group). [4] Studies have also shown that rates of adherence and rates of rejection are comparable between ALD and non-ALD groups. [5] The most common causes of death for patients who undergo ALD LT are de novo malignancies and cardiovascular disease; however, this may also be confounded by the high comorbidity of nicotine use disorder in these patients.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…[3] In a 2023 study of 506 LT recipients (97 of whom had ALD), 1 year, 3 year, and 5 year survival rates posttransplant were also similar (87.7%/84.3%/79.5% for ALD group vs. 82.8%/76.6%/ 72.2% in the non-ALD group). [4] Studies have also shown that rates of adherence and rates of rejection are comparable between ALD and non-ALD groups. [5] The most common causes of death for patients who undergo ALD LT are de novo malignancies and cardiovascular disease; however, this may also be confounded by the high comorbidity of nicotine use disorder in these patients.…”
mentioning
confidence: 97%
“…Reported rates of relapse on alcohol posttransplant were quite variable across studies. The percentage of any drinking posttransplant, ranged from 30% to 50% 4,7,8 . However, the percentage of patients who return to heavy drinking was less, ranging from 6% to 30% 8 .…”
mentioning
confidence: 98%
See 3 more Smart Citations